2012
DOI: 10.5812/iranjradiol.8070
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Coronary Artery Anomalies and Variants in 2697 Consecutive Patients Using 64-Detector Row Coronary CTAngiography

Abstract: BackgroundCoronary artery anomalies are not common, but could be very serious.ObjectivesThis study determines the frequency of coronary anomalies and normal variants by multi-detector-row computed tomography (MDCT).Patients and MethodsThe results of cardiac MDCT study in 2697 consecutive patients were analyzed retrospectively. Acquisition was performed by a 64-detector row CT machine. Imaging results were assessed by experienced radiologists.ResultsMyocardial bridging was by far the most frequent coronary vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
(81 reference statements)
3
21
0
4
Order By: Relevance
“…2,3 The incidence of coronary artery fistulae is reported to be less than 1% in several studies. [3][4][5] A review of the literature shows that there is no uniform consensus regarding the most common site of origin. However, the left main coronary artery is reported to be the most common site of origin in several studies, whereas the most common site of drainage is the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The incidence of coronary artery fistulae is reported to be less than 1% in several studies. [3][4][5] A review of the literature shows that there is no uniform consensus regarding the most common site of origin. However, the left main coronary artery is reported to be the most common site of origin in several studies, whereas the most common site of drainage is the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
“…The MB was the most frequently found anomaly as it was diagnosed in 78 (9%) cases in the current study. In contrast, Shabestari et al [34] found much higher incidence (21.3%).…”
Section: Discussionmentioning
confidence: 67%
“…Several studies only consider anomalies of origin and course, based on the Angelini et al classification 3 , or only disregard MBLAD as anomaly. [12][13][14][15][16][17][18][19] In addition, there are studies that use their own classification, [20][21][22][23] making it challenging to compare data unless one performs a re-analysis of the results using the same classification.…”
Section: Discussionmentioning
confidence: 99%